1806 Molecular Mechanisms of Perinatal Lung Fluid Clearance in term Newborns. (October 2012) - Janér, C; Helve, O; Süvari, L; Pitkänen, OM; Andersson, S
Abstract : Background and Aim: The perinatal switch from secretion to absorption in airway fluid transport includes increase in gene expression and activity of ion channels, e.g. apical amiloride-sensitive epithelial sodium channel (ENaC) and basolateral Na-K-ATPase. The serum- and glucocorticoid-induced kinase (SGK) may induce ENaC and Na-K-ATPase. Our objective was to study airway expression of SGK1, Na-K-ATPase α1-subunit and αENaC during adaptation in term infants. Methods: 86 term infants (GA= 39.43±0.91; mean ± SD) were included in the study (vaginal delivery, VD, n=25 and elective cesarean section, CS, n=61). Within 3 hours and at 22–29 hours after delivery airway cell samples were obtained from the infants' nasal epithelium. αENaC, Na-K-ATPase α1-subunit, and SGK1 mRNAs in the samples were quantified with real-time RT-PCR and normalized to cytokeratin 18 (CK18). Results: ENaC and Na-K-ATPase α-subunit mRNA amounts were similar after VD and CS. During the first postnatal day Na-K-ATPase α1 gene expression decreased in infants delivered by CS (p<0.001). After CS SGK1 mRNA was higher at < 30 min than at 1–3 hours of age (p<0.001). Within 3 hours after vaginal delivery ENaC and Na-K-ATPase α-subunit mRNA correlated with SGK1 mRNA (r = 0.46, p= 0.04, and r=0.63, p=0.005, respectively). Conclusions: Na-K-ATPase α1 is highest during early adaptation coinciding with the challenge of fluid absorption during immediate postnatal life. High SGK1 may be related perinatal stress. SGK1 dependent induction of ENaC and Na-K-ATPase may be an important physiological mechanism for lung fluid clearance.